Splicing factor SNRPA associated with microvascular invasion promotes hepatocellular carcinoma metastasis through activating NOTCH1/Snail pathway and is mediated by circSEC62/miR‐625‐5p axis. Issue 5 (30th January 2023) - Mo, Zhaohong; Li, Ruixi; Cao, Chuanlin; Li, Yanjie; Zheng, Shiyang; Wu, Runxin; Xue, Jinhua; Hu, Jingxiong; Meng, Hongyu; Zhai, Hang; Huang, Weiling; Zheng, Fang; et al.
Abstract: Microvascular invasion (MVI) is a crucial risk factor related to the metastasis of hepatocellular carcinoma (HCC), but the underlying mechanisms remain to be revealed. Characterizing the inherent mechanisms of MVI may aid in the development of effective treatment strategies to improve the prognosis of HCC patients with metastasis. Through the Gene Expression Omnibus (GEO) database, we identified that small nuclear ribonucleoprotein polypeptide A (SNRPA) was related to MVI in HCC. SNRPA was overexpressed in MVI‐HCC and correlated with poor patient survival. Mechanistically, SNRPA promoted the epithelial‐mesenchymal transition (EMT)‐like process for HCC cells to accelerate metastasis by activating the NOTCH1/Snail pathway in vitro and in vivo . Importantly, circSEC62 upregulated SNRPA expression in HCC cells via miR‐625‐5p sponging. Taking these results together, our study identified a novel regulatory mechanism among SNRPA, miR‐625‐5p, circSEC62 and the NOTCH1/Snail pathway in HCC, which promoted metastasis of HCC and may provide effective suggestions for improving the prognosis of HCC patients with metastasis.